2020
DOI: 10.1088/1755-1315/510/5/052067
|View full text |Cite
|
Sign up to set email alerts
|

Study on the response mechanism of tunnel blasting dynamics and the spatial variation characteristics of the surrounding rock

Abstract: The construction of the new Orfa drill explosion is the main method of tunneling in mountainous areas at present, and the vibration waves produced by blasting have a great influence on the deformation and stability of the surrounding rock. Based on the tunnel project at the Dalong Expressway in Guizhou, China, the vibration and deformation parameters of the surrounding rock in the blasting construction process are monitored, and the dynamic response mechanisms are studied. Simulations are carried out using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…13 Zhang simulated the construction process of tunnel blasting, the numerical results found that the exponential load waveform can more completely show the spatial variability characteristics of surrounding rock than the smooth curve load waveform and the triangular load waveform, and the deformation size is consistent with the actual working condition. 14 He et al studied the variation law of explosion load and transient unloading stress field of in-situ stress caused by multi-stage blasting on the excavation surface. The research results found that when the local stress continues to increase, the contribution of transient unloading of geostress to the damaged region will become more and more obvious.…”
Section: Introductionmentioning
confidence: 99%
“…13 Zhang simulated the construction process of tunnel blasting, the numerical results found that the exponential load waveform can more completely show the spatial variability characteristics of surrounding rock than the smooth curve load waveform and the triangular load waveform, and the deformation size is consistent with the actual working condition. 14 He et al studied the variation law of explosion load and transient unloading stress field of in-situ stress caused by multi-stage blasting on the excavation surface. The research results found that when the local stress continues to increase, the contribution of transient unloading of geostress to the damaged region will become more and more obvious.…”
Section: Introductionmentioning
confidence: 99%